Factors that Influence Fluctuations in Employee Commitment - Norma Epriliyana, Nike; Puspa Dewi, Yunita (Universitas Nusantara PGRI Kediri, 2024)
Research aim : The purpose of this study is to explore factors that can influence fluctuations in employee commitment Design/Methode/Approach : This study was conducted qualitative approach through a review of 30 articles published in the last 10 years between 2013 – 2023. Research Finding : The employee organizational commitment able to fluctuate along with company developments and policies. Some factors that influence fluctuations in employee commitment include job satisfaction, leadership, organizational culture, work motivation, job stress, compensation, career development. Theoretical contribution/Originality : this study explore factors that influence fluctuations in employee commitment include job satisfaction, leadership, organizational culture, work motivation, job stress, compensation, career development. Practitionel/Policy implication : The results provide information to managers related to factors that influence fluctuations in employee commitment. The results of the study are expected to be a suggestion for company managers to establish policies that able to maintain the stability of organizational commitment Research limitation : This study used secondary data through systematic literature review of articles for the last 10 years